Development of Edu-Fertiblox digital game using roblox as a teaching aid for the fertigation system topic in the design and technology subject form 1 - Hafiz Athram Nasir,; Fardila Mohd Zaihidee,; Siti Fairuz Yusoff,; Hisbulloh Als Mustofa,; Shafeeqa Shahruddin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
A lack of practical facilities frequently causes problems for teachers and students. The Edu-Fertiblox digital game has been developed for the purpose of being a teaching aid (TA) for the topic of Fertigation Systems in Design Technology Subject Form 1. This study aimed to identify the needs of TAs for the topic of fertigation systems, develop the Edu-Fertiblox digital game as a TA, and assess the usability of the digital game. The development of this game is using the ADDIE model as a research design. The digital game was developed using Roblox Studio. After that, Edu-Fertiblox was evaluated for its usability by three informants, consisting of teaching staff who are experts in Design and Technology. The findings showed all the informants agreed that the Edu-Fertiblox digital game can be used as a teaching aid for the Fertigation System topic of Design and Technology Form 1.